2010
DOI: 10.1158/1078-0432.ccr-09-3192
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multiplexed Tumor-Associated Autoantibody-Based Blood Test for the Detection of Non–Small Cell Lung Cancer

Abstract: Purpose: Non-small cell lung cancer (NSCLC) has an overall 5-year survival of <15%; however, the 5-year survival for stage I disease is over 50%. Unfortunately, 75% of NSCLC is diagnosed at an advanced stage not amenable to surgery. A convenient serum assay capable of unambiguously identifying patients with NSCLC may provide an ideal diagnostic measure to complement computed tomography-based screening protocols.Experimental Design: Standard immunoproteomic method was used to assess differences in circulating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 43 publications
1
72
0
Order By: Relevance
“…Recently, we and others have used proteomic approaches to identify biomarkers for various cancer types (14)(15)(16)(17)(18)(19)(20). In our own proteomic effort, we identified 5 candidate markers that appear to be elevated in serum of lung cancer patients, in comparison to control subjects (6).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we and others have used proteomic approaches to identify biomarkers for various cancer types (14)(15)(16)(17)(18)(19)(20). In our own proteomic effort, we identified 5 candidate markers that appear to be elevated in serum of lung cancer patients, in comparison to control subjects (6).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been applied to early detection and treatment of cancers of the ovary, pancreas, prostate, oesophagus, breast, liver and rectum [21][22][23][24].…”
Section: Technologies Involved In Proteomicsmentioning
confidence: 99%
“…However, despite many leads, little has been done to validate these findings and to translate these promising antibodies into clinically usable tests. Farlow et al [23] identified and validated a large number of potential tumor autoantibodies for NSCLC. Three of these autoantibodies (MTAP, fumarate hydratase and endoplasmic reticulum protein 29) represent new autoantigen targets for distinguishing NSCLC from control populations.…”
Section: Potential Of Lung Cancer Protein Biomarkersmentioning
confidence: 99%
“…Autoantibodies to known or unknown tumor-associated antigens (TAA) are present in sera of patients with some malignancies (7)(8)(9)(10)(11)(12)(13)(14). Various technologies such as serologic analysis of recombinant cDNA expression libraries (SEREX), phage display, and protein arrays have been used to identify autoantibody signatures for cancer diagnosis (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%